2012
DOI: 10.3174/ajnr.a3156
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Fractures Post–Vertebral Augmentation: Analysis of a Prospective Randomized Trial in Osteoporotic Vertebral Compression Fractures

Abstract: BACKGROUND AND PURPOSE:Two injectable materials for the treatment of vertebral compression fractures, Cortoss and PMMA, were compared in a prospective, randomized study. Our purpose was to analyze the incidence and nature of subsequent fractures following treatment, one of the secondary outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…54 Cortoss (Orthovita; Malvern, PA), a bioactive, injectable, nonresorbable composite consisting of highly cross-linked resins and reinforcing bioactive glass fibers, was also found to have a more physiologic load transfer, and patients treated with Cortoss were less likely to be hospitalized for new vertebral compression fractures. 55 …”
Section: Operative Managementmentioning
confidence: 99%
“…54 Cortoss (Orthovita; Malvern, PA), a bioactive, injectable, nonresorbable composite consisting of highly cross-linked resins and reinforcing bioactive glass fibers, was also found to have a more physiologic load transfer, and patients treated with Cortoss were less likely to be hospitalized for new vertebral compression fractures. 55 …”
Section: Operative Managementmentioning
confidence: 99%
“…Silicone resin is a feasible option for the treatment of osteoporotic fractures, which has biomechanical potential to reduce the risk of secondary adjacent vertebral fractures [22]. Gilula et al used cortoss cement and PMMA (polymethyl methacrylate) bone cement for surgery, and found that the incidence of secondary adjacent vertebral fractures in the cortoss cement group was lower than that in the PMMA bone cement group [23]. The optimal amount of bone cement is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, increased cement volume fractures were also found to increase adjacent fractures (33). In acute cases, the dispersed fill pattern and load-bearing properties of the bioactive composite may also result in fewer subsequent fractures (23,34). Secondly, repeated compressive loading over the fracture site can lead to bone loss near the end plate.…”
Section: Discussionmentioning
confidence: 99%